Environmental Sustainability: How Greenpeace Id Conducts Campaigns Regarding Plastic Waste Management through Social Media in Indonesia - Eko Priyo Purnomo; Suswanta Suswanta; Nuryanti Mustari; Inrinofita Sari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Indonesia is estimated to be one of the largest plastic-producing countries in the world. The high use of plastic will cause people to become dependent on plastic. However, dependence on plastic has a destructive impact, which makes plastic potentially harmful to human health and the environment; Greenpeace shares this concern and makes it the basis for organizing a campaign. This study aims to analyze and see how the Greenpeaceid account interacts with Twitter social media accounts through mentions and hashtags used to drive for handling plastic waste in Indonesia. This study uses qualitative research, which uses Q-DAS (Qualitative Data Analysis Software) to analyze the data; the software used is Nvivo 12 Plus. The result of this research is that Greenpeaceid uses social media as a media campaign related to the issue of plastic waste pollution. The social media used by Greenpeace is twitter; on this social media, the form of a campaign is carried out by using #Pantangplastik and #Breakfreefrompalstic, which contains various documentation related to suitable actions in managing plastic waste so that the environment is not polluted again. The existence of the #Pantangplastik Campaign will gradually reduce the use of plastic waste.